PENGARUH PEMBERIAN VAM (Vesicular Arbuscular Mycorrhiza) DAN CHITOSAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KENCUR (Kaempferia galanga L.) - Lodan, Stefanus; Agastya, I Made Indra; Fikrinda, Wahyu (BUANA SAINS, 2023)
The aim of this study was to determine the effect of giving VAM (mycorrhizal arbuscular vesicular) and chitosan on the growth and yield of kencur plants (Kaempferia galanga L.). The research design used factorial randomized block design (RBD) with two treatment factors. The first factor included VAM dose consisting of (V0: 0 g/plant, V1: 10 g/plant, V2: 20 g/plant, V3: 30 g/plant) and the second factor was the dose of chitosan consisting of (C0: control, C1: immersion dose of 25 ml/L, C2: immersion dose of 25 ml/L + follow-up spraying, C3: immersion dose of 50 ml/L, C4: immersion dose of 50 ml/L + follow-up spraying). The results showed the treatment of VAM (mycorrhizal arbuscular vesicular) and chitosan gave an interaction for all observation parameters however the disease incidence component (%) had no significant effect. The best results found in the combination treatment dose of VAM 30 g/tan and Chitosan soaking dose of 50 ml/L (C3V3) with the highest average value on the number of leaves, namely 30.3 leaves, the number of tillers, namely 32.7 tillers, leaf area at the age of 5 BST that is 521.4 cm2and increased to 666.0 cm2 at the age of 6 BST, the fresh weight of the stover was 239.5 g and the dry weight of the stover was 38.6 g, the fresh weight of the rhizomes reached 85.8 g and the dry weight of the rhizomes was 34.6 g, and the production yielded a value of 10,292 tons ha1. The application of mycorrhiza on kencur plants is able to suppress pathogen infection with an average disease incidence ranging from 0-0.6%.